Prayers and the construction of Israelite identity - Gillmayr-Bucher, Susanne, 1962-; Häusl, Maria, 1964- (Atlanta : SBL Press, 2019)
This collection of essays from an international group of scholars focuses on how biblical prayers of the Persian and early Hellenistic periods shaped identity, evoked a sense of belonging to specific groups, and added emotional significance to this affiliation. Contributors draw examples from different biblical texts, including Genesis, Samuel, Kings, Chronicles, Ezra and Nehemiah, Psalms, Jonah, and Daniel.
Shaping biblical books through prayer -- Introduction / Susanne Gillmayr-Bucher, Maria Häusl -- Rhetorically and ideologically shaping the narrative through direct and indirect prayer speech in Chronicles / Michael D. Matlock -- Prayers in the book of Jonah : reflections on different "Israelite" identities? / - Dirk J. Human - So I prayed to the God of heaven (Neh 2:4) : praying and prayers in the books of Ezra and Nehemiah / Maria Häusl -- Identity and social justice in postexilic Yehud : reading Nehemiah 9 in an African liberationist perspective / Ndikho Mtshiselwa -- (Re)modeling biblical figures through prayers. --Testing tales : Genesis 22 and Daniel 3 and 6 / Christo Lombaard -- Glory and remorse : transitions in Solomon's prayer (1 Kgs 8) / Susanne Gillmayr-Bucher -- Hannah's prayer(s) in 1 Samuel 1-2 and in Pseudo-Philo's Liber antiquitatum biblicarum / Hannes Bezzel -- (Re-)constructing identity in the prayers of the Psalter. --
Psalm 37 and the devotionalization of instruction in the postexilic period / Scott C. Jones -- To sanction and to subvert : the reuses of Psalm 132 in the Hebrew Bible / Melody D. Knowles -- Aspects of dynamic remembering and constructing in Psalm 145 : a contribution to the study of prayer in Persian and Hellenistic times / Nancy Rahn.
Includes bibliographical references and indexes.
Keywords: Bible -- Prayers -- History and criticism; Biblija -- Molitva -- Povijest i kritička analiza; Bible -- Criticism, interpretation, etc; Biblija -- Kritička analiza, interpretacija; Jews -- Identity; Židovstvo -- Identitet; Identification (Religion); Identifikacija -- Religija